Assessing library impact on student learning outcomes: a case study using the Understanding Library Impacts Protocol - Rodriguez, Derek; Norberg, Lisa (Qualitative and Quantitative Methods in Libraries, 2017)
Barnard's motto, Following the Way of Reason (Hepomene toi logismoi), is indicative of the College‟s commitment to the broad intellectual rigor and analytical depth of a liberal arts education. In 2012, Barnard College initiated an undergraduate program designed to help students acquire Empirical Reasoning (ER) competencies across the curriculum.  Barnard faculty in several social science disciplines designed ER learning experiences embedded within the undergraduate curriculum for this purpose.  The Barnard College Library created an Empirical Reasoning Lab managed by a Data Librarian to support this curriculum.  A suite of instruments called the Understanding library Impacts Protocol was adapted to assess the impact of the ERL on student learning.  This paper presents methods used in the project, shares preliminary findings from its first year, and discusses future plans.